Challenges and barriers in BIM adoption and implementation in railways - Lin, Yi-Hsuan; Khongsomchit, Lalitphat; Kaewunruen, Sakdirat; Plummer, Paul (Frontiers in Built Environment, 2025)
IntroductionBuilding Information Modelling (BIM) has emerged as a multidisciplinary methodology that integrates information-rich data with virtual representations to support the management of built assets throughout their lifecycle. While BIM is increasingly adopted in architecture, engineering, and construction (AEC) industries and demonstrates significant value in infrastructure projects; however, its application in the railway sector remains limited. The complexity of railway networks, combined with the growing demand for transit projects, presents unique challenges that hinder effective implementation.MethodsThis study investigates the barriers of BIM adoption within the railway industry through a structured questionnaire distributed to professionals and a subsequent detailed analysis of responses.ResultsThis study identifies critical gaps in current BIM practices and highlights several severe obstacles that require urgent attention. Feedback reveals key challenges across four main areas: (1) Technology, (2) Market, (3) Socio-cultural factors, and (4) Policy.DiscussionBy outlining these barriers and suggesting potential solutions, the study provides valuable insights for stakeholders and identifies future research directions to advance BIM integration in railway projects.